Insurance Industry and Non-Agriculture Sector of Nepal: An Empirical Study - Gaire, Hom Nath (Banking Journal, 2013)
In this paper, an attempt has been made to analyse relationship between Nepalese insurance industry and the non-agriculture sector using the annual data of the period of 1997 to 2010. In order to accomplish this goal, unit root test, co-integration test, granger causality test, and ordinary least square method of regression analysis have been performed. The empirical result from the co-integration tests clearly shows that there is a long-run relationship between total premium collection and Resources/Liabilities of Nepalese insurance industry vis-á-vis non-agriculture real GDP. Likewise, the null hypotheses that the total premium collection and Resource/Liabilities does not granger cause non-agriculture and real GDP of Nepal and was rejected. Moreover, estimated coefficients of regression models also indicate that there is strong positive correlation between the insurance industry and non-agriculture sector of Nepal. DOI: http://dx.doi.org/10.3126/bj.v3i1.7510 Banking Journal Vol.3(2) 2013 pp.43-60